2017
DOI: 10.1136/bmjgh-2016-000260.85
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Tuberculosis (Mdr-Tb): An Emerging Problem in West Africa

Abstract: Background Multidrug-resistant tuberculosis (MDR-TB) remains a clear threat to TB control. There is a paucity of data A32

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Although the WHO estimated 20.5% MDR-TB for retreatment cases (classified as patients who have been previously treated for TB and have reported again with the disease), the network reported 35% for the eight West African countries (28,180). In another study that screened isolates from the eight West African countries from 2012 to 2014, the authors also reported the same 6% MDR-TB for new cases and 34% for retreatment cases (30). This shows the prevalence of drug resistance in West Africa has been fairly constant and multidrug resistance has become an emerging health challenge in West Africa.…”
Section: Mechanism Of Drug Resistance Emergence and Evolutionmentioning
confidence: 82%
See 2 more Smart Citations
“…Although the WHO estimated 20.5% MDR-TB for retreatment cases (classified as patients who have been previously treated for TB and have reported again with the disease), the network reported 35% for the eight West African countries (28,180). In another study that screened isolates from the eight West African countries from 2012 to 2014, the authors also reported the same 6% MDR-TB for new cases and 34% for retreatment cases (30). This shows the prevalence of drug resistance in West Africa has been fairly constant and multidrug resistance has become an emerging health challenge in West Africa.…”
Section: Mechanism Of Drug Resistance Emergence and Evolutionmentioning
confidence: 82%
“…Drug sensitive active TB cases are treated with a 6-month multi-drug therapy which includes INH, RIF, pyrazinamide (PZA), and ethambutol (EMB) (26) which has ∼85% treatment success (4). However, there are recent reports of the emergence and high burden of drug resistant TB in the regions (27)(28)(29)(30). Drug-resistant TB remains a public health threat.…”
Section: Control Of Tuberculosis and Its Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a lack of data on the incidence of drug-resistant TB in many countries, particularly in sub-Saharan Africa. 4 Multi-drug resistant TB emerges primarily from poor management of those affected by the disease, which requires appropriate diagnosis and timely treatment in order for effective containment. Thus, efforts must be focused on the correct medications in each new case.…”
Section: Introductionmentioning
confidence: 99%
“…Drug resistant tuberculosis (DR-TB) is a threat to tuberculosis (TB) control with ~ 500,000 cases of rifampicin resistance (RR) reported in 2019 [ 1 ]. In some parts of sub-Saharan Africa (SSA), the prevalence of DR-TB has been reported to be 20% among new TB patients, 53% among previously treated TB patients and the rate of decline of multi-drug resistant TB (MDR-TB) in SSA is dismal [ 2 , 3 ]. The MDR-TB treatment success rate is low and only 57% of patients on conventional treatment regimens have a successful outcome [ 4 ].…”
Section: Introductionmentioning
confidence: 99%